F-term equations near Gepner points - Hori, Kentaro; Walcher, Johannes (Journal of high energy physics, 2005)
We study marginal deformations of B-type D-branes in Landau-Ginzburg orbifolds. The general setup of matrix factorizations allows for exact computations of F-term equations in the low-energy effective theory which are much simpler than in a corresponding geometric description. We present a number of obstructed and unobstructed examples in detail, including one in which a closed string modulus is obstructed by the presence of D-branes. In a certain example, we find a non-trivial global structure of the BRST operator on the moduli space of branes.
Gesehen am 21.02.2020